SELECTED FACTORS RELATED TO FRAILTY OLDER PERSONS IN PUBLIC RESIDENTIAL HOME - เนตรจันทร์ ประกายมาศ; ทาโต รัตน์ศิริ; สาสัตย์ ศิริพันธุ์ (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2019)
The purposes of this descriptive study were to examine frailty and relationships between factors related to frailty which were age, gender, co-morbidity, depression, and social support in older persons living in public residential home in Bangkok Metropolis. The sample consisted of 150 people who were over 60 years old living in public residential home in Bangkok Metropolis. Data were collected using a personal information form, Thai Geriatric Depression, Social support questionnaire and Fried frail index. Their Cronbach’s alpha coefficients were .80, .83, and .80, respectively. Fried frail index was examined for reliability using Inter-rater method. Its coefficient was .96. Mean, percentage, standard deviation, and binary logistic regression were used for data analysis. Research finding were as follows: The prevalence of frailty in older person living in public residential home in Bangkok Metropolis was 58.7 percent. Age was positively and significantly related to frailty in older person living in public residential home in Bangkok Metropolis at the level of .05. When age increasing one year, there is a 10 percent chance for frailty. Social support was negatively and significantly related to frailty in older person living in public residential home in Bangkok Metropolis at the level of .05. By increasing one unit of social support, frailty in the elderly reduces 5 percent.